2019
DOI: 10.1039/c9ta08049j
|View full text |Cite
|
Sign up to set email alerts
|

K+ pre-intercalated manganese dioxide with enhanced Zn2+ diffusion for high rate and durable aqueous zinc-ion batteries

Abstract: α-K0.19MnO2 nanotubes with high K+ content as cathodes for zinc-ion batteries show high capacity, excellent rate capability and cycling stability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
130
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 168 publications
(134 citation statements)
references
References 54 publications
4
130
0
Order By: Relevance
“…Reproduced with permission. [ 82 ] Copyright 2019, Royal Society of Chemistry. e) Structural illustration of zinc ion stabilized MnO 2 .…”
Section: Defect Engineering On Manganese‐based Oxidesmentioning
confidence: 99%
See 3 more Smart Citations
“…Reproduced with permission. [ 82 ] Copyright 2019, Royal Society of Chemistry. e) Structural illustration of zinc ion stabilized MnO 2 .…”
Section: Defect Engineering On Manganese‐based Oxidesmentioning
confidence: 99%
“…Liu et al reported a tunnel‐structure α‐MnO 2 with high preintercalated K + content (α‐K 0.19 MnO 2 ) as a superior cathode for ZIB. [ 82 ] The tunnel structure was shown to have transformed into layer structure after cycling. As such, the preintercalated K + were introduced into the layer space as pillars which could help to stabilize the layer structures.…”
Section: Defect Engineering On Manganese‐based Oxidesmentioning
confidence: 99%
See 2 more Smart Citations
“…[ 17 ] Liu et al have reported that the structural stability can be improved by pre‐intercalated K + into the tunnel structure α‐MnO 2 . [ 18 ] Although the cycling performance was improved to a certain degree, the structure still undergoes an unstable transformation (i.e., transformation into layered structure δ‐MnO 2 ), when further intercalated in Zn 2+ . Therefore, structural stability is one of the key factors in the design of Zn‐HSCs electrode materials.…”
Section: Introductionmentioning
confidence: 99%